Effects of chemical sanitization using NaOH on the properties of polysulfone and polyethersulfone ultrafiltration membranes. (13th November 2014) - Teella, Achyuta; Zydney, Andrew L.; Zhou, Hongyi; Olsen, Cathryn; Robinson, Craig
<x xml:space="preserve">Abstract</x> Membranes used in bioprocessing applications are typically sanitized before use to insure aseptic operation. However, there is almost no information in the literature on the effects of this preuse sanitization step on the properties of the membrane. Experiments were performed with commercially available hollow fiber polysulfone (PSf) and polyethersulfone (PES) membranes with different nominal molecular weight cutoffs. Data were obtained for the membrane hydraulic permeability, dextran retention coefficients, zeta potential (surface charge), and extent of protein adsorption both before and after sanitization with 0.5 N NaOH at 45°C for 30 min. Changes in chemical composition were examined using ATR‐FT‐IR and XPS. Sanitization caused a large increase in the net negative charge for all membranes. There was a small reduction in hydraulic permeability and a significant increase in dextran retention for the polyethersulfone membranes, consistent with a reduction in the effective pore size. Spectroscopic analyses suggest that this change is likely due to the base‐catalyzed hydrolysis of the lactam ring in polyvinylpyrrolidone (PVP) that is typically is used as a wetting/pore‐forming agent in PSf and PES membranes. Preuse sanitization also appeared to have a small effect on protein adsorption, although the extent of adsorption was quite low for both the virgin and sanitized membranes. The observed changes in membrane properties could have a significant impact on the ultrafiltration performance, demonstrating the importance of standardizing the sanitization procedures even in process development and scale‐down validation studies. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:90–96, 2015